Trade Shocks and Macroeconomic Fluctuations in Africa - M. Ayhan Kose; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper examines the role of external shocks in explaining macroeconomic fluctuations in African countries. We construct a quantitative, stochastic, dynamic, multi-sector equilibrium model of a small open economy calibrated to represent a typical African economy. In our framework, external shocks consist of trade shocks, modeled a s fluctuations in the prices of exported primary commodities, imported capital goods and intermediate inputs, and a financial shock, modeled as fluctuations in the world real interest rate. Our results indicate that while trade shocks account for roughly 45 percent of economic fluctuations in aggregate output, financial shocks play only a minor role. We also find that adverse trade shocks induce prolonged recessions.
Keywords: 330; Trade shocks; dynamic stochastic quantitative trade model; African economies